Diversity and potential of indigenous and minor vegetables of Himachal Pradesh - Sharma, Akhilesh; Sharma, Shweta (Indian Horticulture, 2020)
There is a need to develop a clear plan for research and development of indigenous and minor vegetable crops through concerted efforts involving all the stakeholders from farmers and consumers to researchers and policy makers. There is a need to exploit these indigenous resources through coordinated efforts for the improvement of existing diversity for more methodized cultivation. Globally these crops would significantly contribute to food and nutritional security. They represent a rich heritage of genetic material which is of global importance. For the promotion of indigenous and minor vegetable crops, it will be important to enhance research and development programme to collect genetic variability, conserve it and utilize for development of improved cultivars or for harnessing fruitful results in future.